Analyzing PEO anodization time to monitor coatings phases, composition, morphology, thickness, and microhardness during the growth of TiO2 pores on the CP-Ti surface - Kuroda, Pedro A.B.; Cardoso, Giovana C. [UNESP]; Rossi, Mariana C.; Afonso, Conrado R.M.; Grandini, Carlos R. [UNESP] (Elsevier, 2024)
The objective of this study was to develop an oxide coating on commercially pure titanium using the plasma electrolytic oxidation (PEO) technique. During the surface treatment process, the time value was varied for 1, 10, 15, 30, 45, and 60 min. The PEO treatment was carried out at a limited current of 2.5 A and a voltage of 300 V. The coatings exhibit the anatase and rutile crystalline structures of TiO2. The coating produced for longer treatment times has higher concentrations of rutile, resulting in surface hardening. The thickness and the roughness of the coatings increased with the increase in treatment time, but there was a reduction in the size of the pores per unit area.
Keywords: CP-Ti; PEO; Surface characterization